Ammonium pentafluoroantimonate - A. Chappell, ISIS Facility (My University, 2017)
Inelastic Neutron Scattering spectrum of Ammonium pentafluoroantimonate, (NH₄)₂SbF₅, measured on the TFXA instrument.
Keywords: TFXA